Food and feeding habits of Decapterus russelli (Ruppell, 1830) along the Malabar coast - Manojkumar, P P (Indian Journal of Fisheries, 2011)
Study on the food and feeding habits of Decapterus russelli showed that it is a carnivore, subsisting mainly on crustaceans, fishes, polychaetes, salps, molluscs and miscellaneous items. Crustaceans were the most dominant item in different size groups. The fish showed preference to other food fishes as they grew. The intensity of feeding was high during most of the months. Feeding intensity was high in juveniles followed by immature, maturing and spent fishes.